Assessing the Use of Biometric Ear Tags as Body Temperature Monitoring Devices in Swine - Amerson, Ellie A (J Anim Sci, 2021)
It is difficult to detect the subtle changes associated with sickness behaviors in individual pigs early enough to prevent disease outbreaks in group housing settings within large production facilities. This failure results in significant losses to the swine industry. Strategies that allow early detection of parameters such as febrile responses could therefore significantly improve herd health and producer profitability. Our objective was to determine if the use of a biometric ear tag capable of measuring temperature could be used to accurately monitor body temperature in swine. To accomplish this, 42-d-old pigs (n = 21) were fitted with biometric ear tags for 35 d. These devices continuously measured auricular skin temperature and allowed data collection via a paired raspberry pi aggregator. During this period, repeated epidermal temperatures were also taken daily on the rump, shoulder, and ear using a clinical grade infrared thermometer. Correlation analysis using the PROC CORR procedure of SAS was then conducted to determine the ability of the biometric device to estimate body temperature relative to estimates from the clinical device. Infrared temperature readings for the ear significantly correlated with those taken at the shoulder (P < 0.0001) and rump (P < 0.0001). Importantly, temperature readings measured by the biometric ear tags also significantly correlated with infrared readings at the ear (P < 0.0001), shoulder (P < 0.0001) and rump (P < 0.0001) with Pearson Correlation coefficients of 0.51, 0.21, and 0.23, respectively. Collectively, these data support the hypothesis that the biometric ear tag device tested during this trial can be used to continuously monitor body temperature in young swine. These results indicate that further efforts to develop these devices as novel herd health monitoring devices is indeed warranted with the next step involving the assessment of their ability to detect physiological changes in body temperature.